1997
DOI: 10.1007/s001060050185
|View full text |Cite
|
Sign up to set email alerts
|

Laservibrometrie

Abstract: A complete battery of audiometric methods is required for the differential diagnosis of different hearing disabilities (including puretone audiometry, impedance, stapes reflex, speech audiometry, brainstam evoked response audiometry, otoacoustic emissions, etc.). In many cases, a comprehensive diagnosis is not possible. Here we describe a new technique based on a laser-Doppler vibrometer that has the potential for non-invasive diagnosis not only middle ear disease but also cochlear pathologies. Disturbance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
11
0
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 13 publications
2
11
0
4
Order By: Relevance
“…Although our early experiments provided initial evidence for a cochlear mechanical component in the frequency response of the umbo (20), more recent studies by others (25,30) have found no difference between umbo vibration in normal hearing subjects and in patients with sensorineural hearing loss. The problem with these latter studies is that they are conducted at sound pressure levels (SPLs) of 80-100 dB, where the cochlear amplifier is effectively short-circuited (3).…”
mentioning
confidence: 54%
See 4 more Smart Citations
“…Although our early experiments provided initial evidence for a cochlear mechanical component in the frequency response of the umbo (20), more recent studies by others (25,30) have found no difference between umbo vibration in normal hearing subjects and in patients with sensorineural hearing loss. The problem with these latter studies is that they are conducted at sound pressure levels (SPLs) of 80-100 dB, where the cochlear amplifier is effectively short-circuited (3).…”
mentioning
confidence: 54%
“…Instead of only using sound pressure measurements to assess the patency of the cochlear amplifier in humans, it has been proposed that vibration measurements of the eardrum, in particular at the umbo, might provide more reliable information (20), particularly at high frequencies where correctly calibrated sound fields are notoriously difficult to achieve (5,21,22). The most modern technology employs a laser Doppler vibrometer (LDV) to measure eardrum vibrations in human subjects (20,(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
See 3 more Smart Citations